PO204 Peripheral neuropathy in complex inherited diseases: an approach to diagnosis. (1st December 2017) - Rossor, Alexander M; Carr, Aisling; Devine, Helen; Chandrashekar, Holkar; Pelayo-Negro, Ana; Pareyson, Davide; Shy, Michael; Scherer, Steven; Reilly, Mary
Abstract : Peripheral neuropathy is a common finding in patients with complex inherited neurological diseases and may be subclinical or a major component of the phenotype. We have devised a clinical approach to the diagnosis of this complex group of patients by addressing key questions including the predominant neurology syndrome associated with the neuropathy e.g., spasticity, the type of neuropathy, and the other neurological and non-neurological features of the syndrome. In this approach, priority is given to the diagnosis of treatable conditions. A clinical approach to inherited diseases in which the neuropathy is the sole feature of the disease (e.g., Charcot-Marie-Tooth disease) is already well established and is therefore not included. Using this approach, the majority of conditions can be divided into one of three major syndromic categories 1) Ataxia and neuropathy, 2) Spasticity and neuropathy and 3) Global neurodevelopmental impairment and neuropathy. A number of patients do not fall easily into one of these three categories and these can be further refined depending on the predominant system involved in addition to the neuropathy e.g., cardiomyopathy and neuropathy. In this approach, we also include a separate category of complex inherited relapsing neuropathy syndromes, some of which may mimic Guillain Barre syndrome, as many will have a metabolic aetiology and be potentially treatable.